Inovasi Pemanfaatan Eceng Gondok Untuk Pemberdayaan Ekonomi Desa - Mardiyono, Aris; Sugiyarti, Gita (Universitas 17 Agustus 1945 Semarang, 2024)
Water hyacinth is an aquatic weed that is often found in tropical and subtropical areas. The existence of this plant often has a negative impact on the environment. Various efforts have been made to overcome the water hyacinth problem, including the use of pesticides. However, inappropriate use of pesticides actually causes plant resistance to pesticides, so that these efforts become less effective in controlling their growth. To overcome this problem, training was held for village communities to use water hyacinth as a basic material for handicrafts. This training aims to change people's views which previously considered water hyacinth as a nuisance plant into an economic opportunity. By processing water hyacinth into a marketable product, it is hoped that the community can increase their income while overcoming environmental problems